2011
DOI: 10.1117/1.3560298
|View full text |Cite
|
Sign up to set email alerts
|

Dark-field illuminated reflectance fiber bundle endoscopic microscope

Abstract: Abstract. We propose a reflectance fiber bundle microscope using a dark-field illumination configuration for applications in endoscopic medical imaging and diagnostics. Our experiment results show that dark-field illumination can effectively suppress strong specular reflection from the proximal end of the fiber bundle. We realized a lateral resolution of 4.4 μm using the dark-field illuminated fiber bundle configuration. To demonstrate the feasibility of using the system to study cell morphology, we obtained s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Previously, a fiber-bundle reflectance imaging system using illumination through the imaging fiber itself without any additional illumination system has been introduced. [7][8][9]. Applying these techniques into a multipositional illumination scheme would be desirable for future study.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a fiber-bundle reflectance imaging system using illumination through the imaging fiber itself without any additional illumination system has been introduced. [7][8][9]. Applying these techniques into a multipositional illumination scheme would be desirable for future study.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Liu et al suggested an alternative method in which the numerical aperture of the fiber bundle is shared between illumination and collection, a technique conceptually similar to darkfield microscopy. 6 Again this system was demonstrated using cell cultures with an apparently higher SNR.…”
mentioning
confidence: 99%
“…Fiber bundles can also be used for fluorescence endomicroscopy under widefield illumination, providing a low-cost alternative to confocal imaging for selected applications. 2 A further possibility, reflectancemode endomicroscopy, has been demonstrated on several occasions, under both confocal 3,4 and widefield 5,6 operation, but has so far failed to have a similar clinical impact.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our current system has separate illumination fibers and imaging fiber, resulting large size and large invasiveness. The illumination through the imaging fiber itself [12][13][14] may solve the problem.…”
mentioning
confidence: 99%